SIFAT FISIK GAMBUT PEDALAMAN PADA LABORATORIUM ALAM HUTAN GAMBUT SEBANGAU, KALIMANTAN TENGAH - Yonodius Paskalis Bay; Nina Yulianti; Suparno Suparno; Fengky Florante Adji; Zafrullah Damanik; Sustiyah Sustiyah (Jurnal Ilmu Lingkungan, 2021)
Indonesia has the largest peat area in the tropical zone, which estimated about 21 million ha, with a percentage of 70% of the peat area in Southeast Asia and 50% of the world's tropical peatlands. This study aims to evaluate the physical properties of soil in each layer of soil and land cover in inland peat swamp forests in LAHG in Central Kalimantan. The research used the profile method (minipit) measuring 120 cm x 120 cm. Each location is given 3 plots on 2 (two) land cover  namely forest and burnt area. The research location is in LAHG. This research was conducted in July-December 2020. Samples were analyzed at the Banjarbaru Research and Development Laboratory. The parameters observed were bulk density, moisture content, fiber content, soil color, infiltration, and hydraulic conductivity. The research data were analyzed statistically by means of regression and correlation analysis. The results showed that the study of the physical properties of inland peat soil in the forest had bulk density ranging from 0.10 to 0.15 g / cm-3, moisture content 541.18-910.00%, fiber content 8-40%, infiltration -0 , 58-29.27 ml / hour, hydraulic conductivity 2.4-66.6 cm / hour with reddish black soil color. Whereas on burnt land, bulk density ranged from 0.10 to 0.15 g / cm-3, moisture content was 500.00-916.67%, fiber content was 12-52%, infiltration was -3.19-60.99 ml. / hr, hydraulic conductivity 2.4-30.6 cm / hr with dark black soil color. The study relationship pattern shows positive and negative.